2007
DOI: 10.1002/mds.21824
|View full text |Cite
|
Sign up to set email alerts
|

Update of the pathophysiology of the Restless-Legs-Syndrome

Abstract: The Restless Legs Syndrome (RLS) is a heterogeneous disease. Symptomatic or secondary forms encompass iron deficiency, uremia, pregnancy, polyneuropathy, and other causes. The so-called idiopathic RLS syndrome preferentially affects patients with a younger onset before the age of 30. Here we summarize pathophysiological results along the anatomical route, beginning at the cortex and followed by the basal ganglia, thalamus, A11 neurones, substantia nigra, brainstem nuclei, and spinal cord. Genetic risk variants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 80 publications
(176 reference statements)
0
32
0
1
Order By: Relevance
“…However, we hypothesized that increased spinal cord excitability (9), particularly in the supraspinal regions of the lumbosacral segments (L4-S1) (4), and altered dopaminergic systems in the brain and spinal cord play a role in the generation of abnormal sensations in the lower abdomen and perineum that are relieved with urination (10). Afferent fibers from the bladder enter the sacral cord via the pelvic nerves and terminate in segments L4-S2, and these fibers relay essential information and sensations for urinary control.…”
Section: Discussionmentioning
confidence: 99%
“…However, we hypothesized that increased spinal cord excitability (9), particularly in the supraspinal regions of the lumbosacral segments (L4-S1) (4), and altered dopaminergic systems in the brain and spinal cord play a role in the generation of abnormal sensations in the lower abdomen and perineum that are relieved with urination (10). Afferent fibers from the bladder enter the sacral cord via the pelvic nerves and terminate in segments L4-S2, and these fibers relay essential information and sensations for urinary control.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to RLS [88], several features of SRED suggest an underlying dopamine dysfunction. First, dopamine mediates impulsive behaviors, such as motor restlessness, smoking, and binge eating [88,89].…”
Section: The Relationship Between Sred and Rlsmentioning
confidence: 99%
“…First, dopamine mediates impulsive behaviors, such as motor restlessness, smoking, and binge eating [88,89]. Second, a PSG study of 35 SRED patients demonstrated that 77% had PSG confirmation of wakeful RLS and periodic limb movement during sleep [4].…”
Section: The Relationship Between Sred and Rlsmentioning
confidence: 99%
“…As the symptoms of RLS respond dramatically to drugs increasing CNS dopamine (levodopa) and dopamine agonists, dopamine system dysfunction or decreased CNS dopamine at nighttime has been implicated in its pathophysiology [2,3]. Therefore, drugs that block dopamine receptors should cause or aggravate symptoms of RLS.…”
Section: Introductionmentioning
confidence: 99%